Redox potentials, laccase oxidation, and antilarval activities of substituted phenols - Prasain, Keshar; Nguyen, Thi D.T.; Gorman, Maureen J.; Barrigan, Lydia M.; Peng, Zeyu; Kanost, Michael R.; Syed, Lateef U.; Li, Jun; Zhu, Kun Yan; Hua, Duy H. (My University, 2012)
Laccases are copper-containing oxidases that are involved in sclerotization of the cuticle of mosquitoes and other insects. Oxidation of exogenous compounds by insect laccases may have the potential to produce reactive species toxic to insects. We investigated two classes of substituted phenolic compounds, halogenated di- and trihydroxybenzenes and substituted di-tert-butylphenols, on redox potential, oxidation by laccase and effects on mosquito larval growth. An inverse correlation between the oxidation potentials and laccase activity of halogenated hydroxybenzenes was found. Substituted di-tert-butylphenols however were found to impact mosquito larval growth and survival. In particular, 2,4-di-tert-butyl- 6-(3-methyl-2-butenyl)phenol (15) caused greater than 98% mortality of Anopheles gambiae larvae in a concentration of 180 nM, whereas 2-(3,5-di-tert-butyl-4-ydroxyphenyl)-2-methylpropanal oxime (13) and 6,8-di-tert-butyl-2,2-dimethyl-3,4-dihydro-2H-chromene (33) caused 93% and 92% mortalities in concentrations of 3.4 and 3.7 lM, respectively. Larvae treated with di-tert-butylphenolic compounds died just before pupation.
Keywords: Anopheles gambiae; Anti-larval activity; Halogenated di- and trihydroxybenzenes; Laccases; Mosquito larvicides; Redox potential; Substituted di-tert-butylphenols